2001
DOI: 10.1090/s0002-9947-01-02786-6
|View full text |Cite
|
Sign up to set email alerts
|

Projective metrics and mixing properties on towers

Abstract: Abstract. We study the decay of correlations for towers. Using Birkhoff's projective metrics, we obtain a rate of mixing of the form:where α(n) goes to zero in a way related to the asymptotic mass of upper floors, f is some Lipschitz norm and g 1 is some L 1 norm. The fact that the dependence on g is given by an L 1 norm is useful to study asymptotic laws of successive entrance times.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(48 citation statements)
references
References 20 publications
0
47
1
Order By: Relevance
“…This result allows us to use the tower method of L.-S. Young [11] and to obtain the decay rate exp(−α √ n) for correlations of bounded Hölder functions. For bounded Lipschitz functions, one can also use the method of V. Maume-Deschamps [12] and obtain the uniform rate of decay at the rate exp(−αn 1/2− ). It is not clear to me, however, how to use either of these methods in the invertible case.…”
Section: Proposition 15 There Exists a Constant C Such That The Follmentioning
confidence: 99%
“…This result allows us to use the tower method of L.-S. Young [11] and to obtain the decay rate exp(−α √ n) for correlations of bounded Hölder functions. For bounded Lipschitz functions, one can also use the method of V. Maume-Deschamps [12] and obtain the uniform rate of decay at the rate exp(−αn 1/2− ). It is not clear to me, however, how to use either of these methods in the invertible case.…”
Section: Proposition 15 There Exists a Constant C Such That The Follmentioning
confidence: 99%
“…The proof follows from the fact that for the transfer operator without the hole L φt , e −β gives an upper bound on the second largest eigenvalue as well as a bound on the essential spectral radius. This is proved in [M,Theorem 1.4 and Section 4.1]. There it is shown that in our setup (since β is very close to 0), a constructive bound on the second largest eigenvalue is given by tanh(R/2) where R = log 1+e −β 1−e −β .…”
Section: Proofs Of Generic Lemmasmentioning
confidence: 54%
“…for some constant n. In fact, also the exponential case is considered in [20] and it is possible also to get the same estimates with the norm · in place of the supremum norm.…”
Section: Applicationsmentioning
confidence: 89%